Risk factors information and analysis of muscle activity in prolonged standing job relating to decision support system / Isa Halim - Halim, Isa (Institute of Graduate Studies, UiTM, 2012)
In industrial workplaces, many workers perform processes jobs in standing position for a long period of time. This working practice is a potential contributor to discomfort and muscle fatigue to workers. Analysis of discomfort and muscle fatigue associated with prolonged standing using conventional method has limitations such as individual assessment, pen and paper based, and time consuming. The objectives of this study are to establish information on risk factors pertaining to discomfort and muscle fatigue associated with prolonged standing, and analyze muscle activity of workers while performing processes jobs in prolonged standing.